Maternal Health in View of COVID 19: Women’s Awareness, Attitude and Self reported behavior - Deepak (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background & Aim:Pregnancy is a distinctperiod of enjoyment and keenness. But for expectant mothers facing the outbreak of corona virus disease, this otherwise happy moment is clouded by terror, anxiety and uncertainty. When pregnant women are infected with viruses from the same family as COVID-19 and other viral respiratory infections, such as influenza, they have a higher risk of serious illness. Most women are unaware of the pregnancy effects of COVID 19 and how to protect themselves and their infants. The purpose of this study was to assess awareness, attitude and self-reported behavior is assessed about impact of COVD 19 on pregnancy and newborn outcomesMethods:Cross sectional research design was employed in the study. Data was collected through online survey from 500 adult women using Total enumerative sampling technique. Self-structuredquestionnaire and likert scale was used.Result: Result showed that most of the women (84.2%) age group 20-30years. 64.8% of women were Graduate and 23% of women were Postgraduate. Mean knowledge score on maternal health 5.52±1.608. Knowledge score of women residing in Urban and rural area was found significant and in different states at p<0.05.The correlation between awareness and attitude which shows weak positive correlation as coefficient value was 0.109.Conclusion : The results of the study revealed that adult women have little knowledge about impact of COVID 19 on maternal health.There was weak positive correlation between knowledge and attitude regarding impact of COVID 19 on maternal health.